Pengaruh Model Problem Based Learning dan Discovery Learning dengan Media Wordwall terhadap Keterampilan Berpikir Kritis (Studi Eksperimen pada Siswa Kelas XI SMA Negeri 7 Surakarta Jurusan Ilmu Pengetahuan Sosial Tahun Ajaran 2023/2024) - Regina Mulia Riska Putri; Sudarno Sudarno; Dini Octoria (Journal on Education, 2024)
This study aims to determine the difference in influence of the problem based learning and discovery learning model using wordwall media on students’ critical thinking skills. The research method used a quasi experimental pretest-posttest type. The population was 11th grade students of SMA Negeri 7 Surakarta who were divided into two sample classes, namely experimental class with 36 students and control class with 36 students. The sampling technique used purposive sampling technique. Instruments or data collection techniques used tests, observation and documentation. The research data analysis techniques used normality test, homogeneity test, and hypothesis tests with t-test and anova. The result of t-test showed that there was a difference between students’ critical thinking skills of experimental class and control class. This can be proven from the result of independent sample t-test with value of t 2,87 (> ttable), and ANOVA test with calculated value of F 8,21 (> Ftable). Therefore, this can be concluded that the application of the the problem based learning and discovery learning model using wordwall media affects students’ critical thinking skills.